2007
DOI: 10.1590/s0103-84782007000600048
|View full text |Cite
|
Sign up to set email alerts
|

Enraizamento de estacas semilenhosas de pessegueiro "Okinawa" sob efeito de lesão e ácido indolbutírico

Abstract: IISemi-hardwood cuttings rooting of peach tree 'Okinawa' under effect of lesion and indolebutyric acid RESUMO Buscando técnicas mais eficientes na propagação

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…Em experimento com estacas de pessegueiro 'Okinawa', Camolesi et al (2007) e Aguiar et al (2005), também não observaram diferenças nas concentrações do AIB quanto à sobrevivência das estacas. Tabela 1.…”
Section: Resultsunclassified
“…Em experimento com estacas de pessegueiro 'Okinawa', Camolesi et al (2007) e Aguiar et al (2005), também não observaram diferenças nas concentrações do AIB quanto à sobrevivência das estacas. Tabela 1.…”
Section: Resultsunclassified
“…Já Baggio et al (1989) encontraram que estacas lesionadas produziam mais brotos do que estacas sem lesão, algo que pode ser explicado pela formação de calos e raízes na região lesionada, visto que ocorre até o local o transporte de auxinas, etileno e carboidratos, que estimulam as células a se diferenciarem e, assim, a formarem raízes (Biasi et al, 2000). Estacas com maior percentagem de enraizamento por estarem lesionadas também foram evidenciadas por Souza et al (1995), trabalhando com ameixeira cultivar Frontier, e por Camolesi et al (2007), trabalhando com pessegueiro 'Okinawa' . Porém, Bastos et al (2009) demonstraram que o ferimento na base de estacas de caramboleira prejudicou a formação de raízes.…”
Section: Discussionunclassified
“…Souza et al (1995), studying rooting of hardwood cuttings of plum trees, found that an incision at the base of the cutting increased rooting by 27%. Camolesi et al (2007), studying propagation by softwood cuttings of Okinawa peach trees, observed the best results in cuttings that had undergone incision. In contrast, Wagner Júnior et al (2004) found that different types of incisions at the base did not affect the rooting or root development of herbaceous cuttings of four blueberry cultivars (Vaccinium sp.…”
Section: Experiments II (Rainy Season)mentioning
confidence: 99%
“…Several vegetative propagation techniques are currently used, but the one that stands out is propagation by cuttings, in which plant segments, under suitable conditions, grow roots and produce a new plant identical to the plant of origin (CHAGAS et al, 2008;PIO et al, 2007). During seedling production, factors such as cultivar, stage of development, substrate, growth regulators, in addition to different environmental conditions inherent to the season, can interfere in the rooting process (BIAZATTI, 2013).…”
Section: Introductionmentioning
confidence: 99%